A bidirectional study on the acquisition of plural noun phrase interpretation in English and Spanish. (May 2013) - IONIN, TANIA; MONTRUL, SILVINA; CRIVOS, MÓNICA
ABSTRACT This paper investigates how learners interpret definite plural noun phrases (e.g., the tigers) and bare (article-less) plural noun phrases (e.g., tigers) in their second language. Whereas Spanish allows definite plurals to have both generic and specific readings, English requires definite plurals to have specific, nongeneric readings. Generic readings in English are expressed with bare plurals, which are ungrammatical in Spanish in preverbal subject position. Two studies were conducted in order to investigate the role of first language transfer in this domain in both English → Spanish and Spanish → English directions. Study 1 used a meaning-focused task to probe learners' interpretation of definite plural nour phrases, whereas Study 2 used a form-focused task to examine learners' judgments of the acceptability of definite and bare plurals in generic versus specific contexts. First language transfer was attested in both directions, at lower proficiency levels, whereas more targetlike performance was attested at higher proficiency levels. Furthermore, learners were found to be more successful in learning about the (un)grammaticality of bare plurals in the target language than in assigning the target interpretation to definite versus bare plurals. This finding is shown to be consistent with other studies' findings of plural noun phrase interpretation in monolingual and bilingual children.